Career paths with a two-body problem: Occupational specialization and geographic mobility - Valeria Rueda; Guillaume Wilemme (W.E. Upjohn Institute for Employment Research, 2021)
We develop a model of joint job search and occupational choice in which job opportunities can be incompatible inside the couple. Typically, incompatibilities may arise because jobs are not in the same location. We show that the existence of incompatible jobs pushes some couples to sacrifice the career of one partner. The model predicts occupational switches throughout the career and at the time of couple formation. Gendered equilibria, whereby all women (or men) choose the accommodating occupation, may arise. Any element of ex-ante unfavorable gender gaps - for instance, due to discrimination or norms - is amplified and can generate large systemic differences in gender composition between occupations.
Keywords: C78; D13; D83; 330; two-body problem; occupational specialization; career path